Laser scanning-based physical unclonable functions for anti-counterfeiting applications - Lee, Bryan Ker Xiang (Nanyang Technological University, 2024)
Physical Unclonable Functions (PUFs) represent an innovative strategy in the battle against counterfeiting, capitalizing on their impossible chances of replicas to produce secure anti-counterfeiting tags. The primary challenge in deploying PUF broadly is the intricacy involved in authenticating these tags, which traditionally requires sophisticated analysis not accessible to the average end-user. This project introduces an innovative method focused on reducing the dimensional complexity of PUF substrates, thereby transforming them into a form that can be quickly and easily verified by end users without compromising security. This will bring authentication to a new level, different from conventional methods that rely solely on visible markers like insignias associated with the product brand.